"Suction Caps": Designing Anisotropic Core/Shell Microcapsules with Controlled Membrane Mechanics and Substrate Affinity. (1st July 2016) - Jerri, Huda A.; Jacquemond, Marlène; Hansen, Christopher; Ouali, Lahoussine; Erni, Philipp
Abstract : Core/shell microcapsules with low‐permeability membranes and controlled morphology are crucial for the delivery and controlled release of fragrance molecules, pharmaceuticals, inks, or vitamins. Design criteria for next generation microcapsules must include chemical and mechanical stability, and also provide enhanced substrate interactions to improve deposition onto relevant complex surfaces. Here, a coupled approach is presented to synthesize core/shell delivery systems by interfacial polymerization to enhance both the microcapsule–substrate interactions and the mechanical properties of the capsules to induce a burst‐type release. By combining membrane synthesis, nonlinear mechanics, interfacial rheology, analysis of mass transfer, and capsule morphology generated during interfacial polymerization, large permanent deformations into the capsule geometry are programmed, resulting in chemically stable, yet mechanically rupturing microcapsules with anisotropic geometry. To promote interactions and capsule adhesion onto complex substrates, the capsule contact area is controlled to form prominent "suction cup" shaped rims. These capsules have favorable, far‐reaching electrostatic interactions with oppositely charged substrates such as glass, hair, skin, or fabric. By modulating membrane mechanical properties and morphology during synthesis, formulation‐independent physical criteria are used to improve the overall performance of a functional delivery system while expanding knowledge of the key parameters influencing the interfacial polymerization process and membrane formation. Abstract : Anisotropic core/shell microcapsules with "suction cup" morphologies provide enhanced affinity on complex substrates, such as the surface of human hair. The mechanics and permeability of the capsule membrane can be designed to synthesize chemically stable, yet mechanically rupturing targeted delivery systems for low‐molecular‐weight payloads.